Structural assessment of earthquake resilience in historic mosques: a study on Şimşirli Mosque - Arzu Er (Journal of Asian Architecture and Building Engineering)
Anatolia, a region where diverse cultures converge, has fostered the development of unique architectural techniques. Among these, the wooden hypostyle building technique stands out as a distinctive synthesis, blending the Asian timber tradition with Byzantine masonry systems. The 19th-century Şimşirli Mosque in Rize, Turkiye, serves as a remarkable example of the sustainability of this tradition. This study evaluates the seismic performance of Şimşirli Mosque through linear, nonlinear, and kinematic analysis methods. The findings indicate that the mosque and its minaret achieve the performance levels of “Limited Damage” under DD-3 earthquake ground motion and “Controlled Damage” under DD-2 conditions. However, kinematic analyses identified overturning, lateral bending, and vertical bending mechanisms in the front and right facade walls. A comprehensive methodology is presented for assessing the seismic resilience of historic mosques, underscoring the cultural and structural importance of preserving the wooden hypostyle tradition for future generations. The findings highlight the critical need for scientifically informed restoration and strengthening processes to ensure the sustainability of this thousand-year-old tradition. This paper is believed to serve as a valuable guide for practitioners, providing clear steps for assessing structural performance during the restoration process.